PENGARUH SENAM HAMIL TERHADAP TINGKAT KECEMASAN PADA IBU PRENATAL TRIMESTER III DI RSIA CAHAYA BUNDA - Dewi, Ni Luh Putu Arista Candra; Pratiwi, Ni Made Sintha; Astuti, Ni Luh Seri (Jurnal Kesehatan Medika Udayana, 2019)
Background: Anxiety is a feeling of discomfort, a feeling of fear caused by anticipation of danger. The impact of anxiety is bad for mother and fetus,  so it needs to do intervention for resolving the anxiety. Pregnant gymnastics is one way to reduce anxiety in pregnant women. Objective: Knowing the effect of pregnancy exercise on the level of anxiety in prenatal mothers in the third trimester at the RSIA Cahaya Bunda Gerokgak Tabanan. Method: The desaign used the pre-experimental design of one pretest posttest group, the research subjects were prenatal mothers in the third trimester, with non probability sampling used a purposive sampling method. The research instrument with the HARS questionnaire. Statistical tests used the Wilcoxon Test, with a confidence level of 95% and p <0.05. Results: The results of the pretest were moderate anxiety of 63.3% and severe anxiety 36.7%, after the intervention, the results of the posttest score were mild anxiety (60.0%), no anxiety (36.7%) and moderate anxiety (3.3%). The Wilcoxon analysis test results get a value of ? = 0,000 and the value of ? is smaller than ? (5%) or 0.05, it means there is a significant effect of pregnancy exercise on the level of anxiety in prenatal mothers in the third trimester. Conclusion: There was a decrease in the level of anxiety before the intervention was given and after the intervention was given, so that there was the influence of pregnancy exercise on the anxiety level of prenatal pregnant women in the third trimester.   Keyword:Anxiety Level, Pregnant Gymnastics, Prenatal in The Third Trimester